Análise da expressão dos receptores envolvidos no controle vesical em pacientes com bexiga desfuncionalizada e do comportamento miccional após o transplante renal - Neves Neto, João Ferreira [UNIFESP] (2017)
Objective: End-stage renal disease (ESRD) patients undergoing dialysis may develop anuria. Long periods of anuria lead to interruption of the physiological storage and voiding cycle, a condition known as defunctionalized bladder (DB). The objective of this study is to evaluate the expression of bladder receptors in patients with DB and to assess voiding behavior after refunctionalization. Methods: A total of 68 patients with ESRD undergoing dialysis who were candidates to kidney transplant were divided in two groups: DB (diuresis < 300 mL/24 h; n=33) and NDB (non-DB; diuresis  300 mL/24 h; n=35). During kidney transplant a sample of the already dissected mucosa and detrusor at the site of the future ureteral implantation were collected. The expression of the following receptors was evaluated by real-time polymerase chain reaction (RT-PCR) in the mucosa and detrusor: M2, M3, 1D, 3, P2X1, P2X2, P2X3, TRPV1, TRPV4, TRPA1 and TRPM8. At 3, 6 and 12 months after kidney transplant patients answered IPSS and ICIQ-OAB questionnaires. They also filled a 3-day 24 h frequency/volume chart at 6 and 12 months. Results: There was no difference in sex and age between DB and NDB groups. Lower diuresis volume in 24 h and longer pretransplant dialysis duration was observed in DB patients. The expression of all receptors in the mucosa and in the detrusor was similar in both groups, except from 1D, which was overexpressed in the detrusor of DB relatively to NDB group. TRPM8 expression was not demonstrated in any bladder layer of any group. ICIQ-OAB symptom score was similar between the groups at 3, 6 and 12 months. There was a reduction of this score in both groups throughout the follow-up. The same pattern was found for IPSS score. Bother scores were similar between groups. No difference was observed for all parameters extracted from the frequency-volume charts between DB and NDB patients. Conclusion: Gene expression of bladder receptors involved in micturition control was similar in patients with or without DB. Bladder behavior had a similar pattern independently of pretransplant residual diuresis. These findings question the relevance of the term DB in pretransplant patients.